Teachers, ICT and Computer-based Testing : An Acceptance Study at Luleå University of Technology - Heikkilä, Martin; Markstedt, Sara (2012)
Information and communication technology (ICT) is intensifying its influence in today's schools. A further step in this direction is to introduce computer-based tests. In this study, we get to grips with trying to identify the factors that influence teachers and their technology acceptance in their work with ICT and computer-based test.The results we have presented in our study is that the most important factor the teachers at Luleå University of Technology perceived to be when it comes to acceptance of computer-based test is how useful a system is. Other important factors are ease of use and that the system is relevant to their work. Less influential factors are whether the system is perceived as fun or social factors like status. Validerat; 20120221 (ysko)